Post Keynesian and ecological economics confronting environmental issues - Holt, Richard P. F., 1953-; Pressman, Steven; Spash, Clive L.; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2009)
It is argued that mainstream economics, with its present methodological approach, is limited in its ability to analyze and develop adequate public policy to deal with current environmental problems and sustainable development. This book provides an alternative approach. Building on the strengths and insights of Post Keynesian and ecological economics and incorporating cutting edge work in such areas as economic complexity, bounded rationality and socio-economic dynamics, the contributors to this book provide a trans-disciplinary approach to deal with a broad range of environmental concerns.
pt. I. Introduction -- pt. II. Methodology and history of thought -- pt. III. Consumers in theory and practice -- pt. IV. Structuring systems of production.
Includes bibliographical references and index.
Keywords: Keynesian economics; Environmental economics; Electronic books